2014
DOI: 10.1002/bdrc.21082
|View full text |Cite
|
Sign up to set email alerts
|

Connecting teratogen‐induced congenital heart defects to neural crest cells and their effect on cardiac function

Abstract: Neural crest cells play many key roles in embryonic development, as demonstrated by the abnormalities that result from their specific absence or dysfunction. Unfortunately, these key cells are particularly sensitive to abnormalities in various intrinsic and extrinsic factors, such as genetic deletions or ethanol-exposure that lead to morbidity and mortality for organisms. This review discusses the role identified for a segment of neural crest is in regulating the morphogenesis of the heart and associated great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 284 publications
(319 reference statements)
2
20
0
Order By: Relevance
“…15 The results indicated that maternal medication in early pregnancy, viral infection, hair dyeing and perm during pregnancy or half a year before pregnancy, house decoration, parents' exposure to environmental pollution are independent risk factors for congenital heart disease in infants and young children. [16][17][18] Multivariate logistic regression analysis showed that the incidence of CHD was associated with hair perm and dyeing, medication taken by mothers in early pregnancy, house decoration, virus infection, and exposure to pollution of working environment. 19 Viral infections and medicines used in early pregnancy have been considered as a vital factor of developing congenital cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…15 The results indicated that maternal medication in early pregnancy, viral infection, hair dyeing and perm during pregnancy or half a year before pregnancy, house decoration, parents' exposure to environmental pollution are independent risk factors for congenital heart disease in infants and young children. [16][17][18] Multivariate logistic regression analysis showed that the incidence of CHD was associated with hair perm and dyeing, medication taken by mothers in early pregnancy, house decoration, virus infection, and exposure to pollution of working environment. 19 Viral infections and medicines used in early pregnancy have been considered as a vital factor of developing congenital cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…It is critical that the embryo generates and maintains a sufficient pool of NC progenitors that survive, proliferate, migrate, and differentiate appropriately [ 29 ] as deficiencies in these processes underlie a number of congenital craniofacial malformation disorders as seen in a number of human syndromes with craniofacial malformations [ 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, as discussed below, there is little clinical evidence that reduced RA levels affect human embryonic development. Second, ethanol exposure may have a directly deleterious effect on cardiac neural crest cells (Karunamuni et al 2014). These are cells that arise in the neural tube but, during early development, migrate into the cardiac OFT and pharyngeal arches, and contribute to the valves, septa, and aortic arch arteries.…”
Section: Alcoholmentioning
confidence: 99%